Three-dimensional acoustic energy flow from rotating sound sources - Ocker Christof (EDP Sciences, 2021)
A detailed study of the three-dimensional sound fields around a monopole point source in subsonic and supersonic rotation is investigated. We calculate the sound pressure, the acoustic velocity, as well as the instantaneous and time-averaged acoustic intensity fields with the advanced time approach. The advanced time approach is applied for sound sources at subsonic and supersonic rotation and yield comparable results as those obtained from the spherical harmonic series expansion method or the solution of the retarded time equation. Further, the direction of the time-averaged acoustic energy flow is derived from the acoustic intensity vectors. It is shown, that the direction of the energy flow path differs from the radial direction and depends on the rotational direction and rotational velocity. Those findings are useful, for example, to improve the acoustic absorption performance of sound absorbers and acoustic liners around turbomachines.